Laying in a new course? A bibliometric analysis of L2 vocabulary research 1988-92 - Paul Meara (LingBaW)
This paper uses an author co-citation analysis to examine the research on L2 vocabulary acquisition published in 1992. Two analyses are presented. The first analysis provides a context for the 1992 data. It looks at work that was being cited in a five year window covering 1988-92. The second analysis is a more detailed account of the 1992 research on its own terms.